Acute High Fat Diet Consumption Activates the Mesolimbic Circuit and Requires Orexin Signaling in a Mouse Model - Valdivia Torres, Lesly Spring (2014)
Overconsumption of palatable energy-dense foods has negative health implications and it is associated with obesity andseveral eating disorders. Currently, little is known about the neuronal circuitries activated by the acute ingestion of arewarding stimulus. Here, we used a combination of immunohistochemistry, pharmacology and neuronal tracing analysesto examine the role of the mesolimbic system in general, and the orexin neurons in particular, in a simple experimental testin which naı ̈ve mice are allowed to spontaneously eat a pellet of a high fat diet (HFD) for 2 h. We found that acute HFDactivates c-Fos expression in several reward-related brain areas, including the ventral tegmental area (VTA), nucleusaccumbens, central amygdala and lateral hypothalamic area. We also found that: i- HFD-mediated orosensory stimulationwas required for the mesolimbic pathway activation, ii- acute HFD differentially activates dopamine neurons of theparanigral, parabrachial pigmented and interfascicular sub-regions of the VTA, and iii- orexin neurons of the lateralhypothalamic area are responsive to acute HFD. Moreover, orexin signaling blockade, with the orexin 1 receptor antagonistSB-334867, reduces acute HFD consumption and c-Fos induction in the VTA but not in the other mesolimbic nuclei understudy. Finally, we found that most orexin neurons responsive to acute HFD innervate the VTA. Our results show that acuteHFD consumption recruits the mesolimbic system and that the full manifestation of this eating behavior requires theactivation of orexin signaling.